Growth of Leishmania tropica Promastigotes in Urine Samples of Different Genders and the Role of Citrate in Culture - Allahverdiyeva, Adil M.; Bagirova, Malahat; Elcicek, Serhat; Oztel, Olga Nehir; Koc, Rabia Cakir; Novruzova, Metanet; Ates, Sezen Canim (Ars Docendi, 2012)
Leishmaniasis is a zoonotic disease caused by an obligatory intracellular protozoon, which threatens 350 million people in 98 countries. Cultivation of Leishmania parasites plays an important role in developing vaccines and drugs against leishmaniasis, in diagnosis and treatment of disease. Even though some studies showed stimulatory effect of human urine in culture, gender differences, standard living and nutrition conditions haven't been considered. There is also insufficient information about which urine components are responsible for stimulating the growth of parasites. Citrate is one of the most important urine components but the effect of citrate on development of parasites hasn't been investigated. In this study, it was determined that urine taken from male and female donors with identical nutritional backgrounds stimulated the proliferation of Leishmania tropica promastigotes and despite the fact that female urine was more effective; urine of some male donors increased the proliferations of parasites too much. In addition we showed that citrate may be one of the urine components which are responsible for parasites development.
Keywords: Human urine; L. tropica; citrate; cultivation